Treatment Initiatives for Patients with Alzheimer’s Disease - Howe, Edmund (Matrix Medical Communications, 2009)
There are several treatment initiatives a psychiatrist should consider when treating a patient with Alzheimer’s disease. The author discusses five treatment initiatives in the order in which they tend to arise during the illness progression of a patient with Alzheimer’s disease: screening for Alzheimer’s disease, providing information to patients on nonevidence-based treatments of Alzheimer’s disease, assisting patients with contacting loved ones as the disease progresses, confronting patients with difficult decisions, and discussing moral concerns of the patient with his or her loved ones. Case examples and a review of literature are also provided.